ANALYSIS OF CHANGE IN THE AREA OF INUNDATION DUE TO LAND SUBSIDENCE IN SEMARANG (A Case Study: Jl. Ahmad Yani, Jl. Erlangga Tengah, Jl. Sugiyopranoto) - Pratikso Pratikso; Rahmat Mudiyono; Dian Indah Permatasari (International Conference on Coastal and Delta Areas, 2017)
Semarang is located on the north coast of Java island and develops in river flow area which genetically has alluvial materials. The process of precipitation continues until now and as a result a fairly thick layer of clay is founded. The layers of clay and land subsidence are related to each other. Land subsidence causes inundation or locally called rob area becoming increasingly widespread. The process of land subsidence causes a loss for the government of Semarang. The purpose of this study was to analyze the change in the area of inundation due to land subsidence in Semarang, on Ahmad Yani Street, Central Erlangga Street, and Sugiyopranoto Street, and give the best advice for the government to develop the city. Method of analysis used in this study was terzaghi method, GIS software (Geography Information System), and Plaxis software. The results showed that the rates of the land subsidence is getting bigger and the time is getting longer. Keywords: Land Subsidence, Terzaghi, Geography Information System, Plaxis